Anti-mycobacteria potential and synergistic effects of combined crude extracts of selected medicinal plants used by Bapedi traditional healers to treat tuberculosis related symptoms in Limpopo Province, South Africa - Komape, Nancy Patience Motlalepula; Bagla, Victor Patrick; Kabongo-Kayoka, Prudence; Masoko, Peter (BMC Complementary and Alternative Medicine, 2017)
Background: Tuberculosis is an infectious communicable disease and the causative agent of the disease has over the years developed resistance to streamline chemotherapeutic agents with dire consequences and there is a need for development of new and more potent alternatives. Methods: Constituents of leaves material of Combretum heroroense, Citrus lemon and Apodytes dimidiata were serially extracted using solvents of varying polarity. TLC finger print profile of the different extracts were determined by spraying eluted plates with vanillin sulphuric acid and 2, 2- diphenylpicryl hydrazyl (DPPH) for the presence of antioxidant constituents. Presence of different phytochemicals was determined using standard chemical test. Bioautography was used to determine the number of compounds present in sub-fractions active against Mycobacterium smegmatis. Minimum inhibitory concentration (MIC) values extract and sub-fractions were determined using serial microplate dilution method against M. smegmatis (ATCC 1441), M. tuberculosis (ATCC H37Rv) and multi-drug resistant TB (MDR-TB) field strain. Synergy of the crude extracts of the three plants was determined using microplate dilution method against M. smegmatis. Results: Mass extracted by different solvents was less than 6% dry weight for all the plants. Phlobatannins were not detected in A. dimidiata, C. heroroense and C. lemon as well as cardiac glycosides in C. lemon and A. dimidiata, and saponins in C. heroroense. Sub-fractions of the different plants were shown to contain constituents with antioxidant activity with the highest number detected in C. heroroense. Bioautography results reveal the presence of a compound(s) in the ethyle acetate sub-fraction of C. heroroense and butanol, methanol/water, ethyl acetate and water no.2 subfractions of A. dimidiata, active againstM. smegmatis that were not shown to have antioxidant capacity. MIC results for different crude extracts of the three plants against M. smegmatis ranges from 0.1 to 3 mg/ml. The average MIC for the synergistic effect of the plants ranged from 0.04 mg/ml to 1.25 mg/ml. An activity greater than that obtained for the reference drugs was shown for the butanol and hexane fractions of A. dimidiata (0.47 mg/ml) against the field strain of MDR-TB while that obtained for the M.TB (ATCC H37Rv) was 0.31 mg/ml. : A significant finding shown in this study reveals the potent anti-mycobacteria potential of sub-fractions of A. dimidiata against MDR-TB field strain that can lead to the isolation of compounds that can be used to counter resistant strains of tuberculosis.
Journal article published in the Journal of BMC Complementary and Alternative Medicine (2017) 17:128
Keywords: Combretum heroroense; Citrus lemon; Apodytes dimidiata; Minimum inhibitory concentration; Bio-autography; Anti-oxidant activity; Multi-drug resistant tuberculosis strain; Multidrug-resistant tuberculosis; Medicinal plants; Lemons; Healers